Determine the Frequency of Hepatitis B and C in Patients Undergoing Hemodialysis - Baig, Muhammad Atif; Ansari, Tanveer Ahmed; Mugheri, Ali Hyder; Jamali, Abdul Hameed; Mushtaq, Fahad; Ali, Shoukat (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of hepatitis b and c in patients undergoing hemodialysis. Study Design: Descriptive study. Place and duration of study: Department of Gastroenterology, Chandka Medical College Hospital/Shaheed Mohtarma Benazir Bhutto Medical University Larkana & Dialysis Unit, Chandka Medical College Hospital, Larkana from 1st October 2020 to 30th September 2021. Methodology: One hundred patients undergoing hemodialysis were tested for hepatitis B and C after their informed written approval gain. The age, gender and clinical history were recorded. Each patient 5cc blood was withdrawn and EDTA was added for creating whole blood which was then stored at 4ºC for a day and tested. The blood was first tested before hemodialysis start and then after every month until 6 months of hemodialysis was tested for presence of hepatitis B and C through polymerase chain reaction (PCR). Results: The mean age was 51.27±12.0 years with 14-77 years of patients enrolled for hemodialysis. Majority of the patients were men with a percentage of 52% while women as 48% in the total cases. The serological results showed that hepatitis B positive was presented as 8% and hepatitis C positive as 4% in total hemodialysis cases. Hepatitis B was more common in those cases where blood transfusion was performed more than 5-10 times or more. Conclusion: Prevalence of HBV was higher in hemodialysis patients who had more blood transfusions.